2023
DOI: 10.1038/s41467-023-42046-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple channelling single-photon emission with scattering holography designed metasurfaces

Danylo Komisar,
Shailesh Kumar,
Yinhui Kan
et al.

Abstract: Channelling single-photon emission in multiple well-defined directions and simultaneously controlling its polarization characteristics is highly desirable for numerous quantum technology applications. We show that this can be achieved by using quantum emitters (QEs) nonradiatively coupled to surface plasmon polaritons (SPPs), which are scattered into outgoing free-propagating waves by appropriately designed metasurfaces. The QE-coupled metasurface design is based on the scattering holography approach with radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…An example of intelligent coding meta-holograms is analyzed by Liu et al [155]. Tunable meta-holograms have also opened pathways to their use in adaptive optics, switchable imaging and advanced 3D displays [156], and, on the other hand, for optical traps [157] and quantum optics [158,159].…”
Section: Meta-hologramsmentioning
confidence: 99%
“…An example of intelligent coding meta-holograms is analyzed by Liu et al [155]. Tunable meta-holograms have also opened pathways to their use in adaptive optics, switchable imaging and advanced 3D displays [156], and, on the other hand, for optical traps [157] and quantum optics [158,159].…”
Section: Meta-hologramsmentioning
confidence: 99%
“…A similar concept has been demonstrated for epitaxial semiconductor QDs [86][87][88][89][90][91][92][93][94][95] and color centers in diamond. [96][97][98] Importantly, by introducing a small asymmetry to the CBG (Figure 4b), it is possible to break the 50% efficiency limit imposed by polarization filtering. Based on this idea, Hui Wang and co-workers reported a QD single photon source emitting polarized single photons with an efficiency of 56% and an indistinguishability near 100%, which paves a way to realize an ideal polarized single photon source.…”
Section: Quantum Dots and Color Centersmentioning
confidence: 99%
“…17 propagating along different off-normal directions with orthogonal linear polarizations, a complex functionality that can be assigned to a chip-integrated micronano single-photon polarization beam splitter. 36 Moreover, the original VSH approach 35 has further been extended and applied to realize quantum light sources for multichannel emission encoded with different spin and orbital angular momenta in each channel, extending multiple degrees of freedoms of QE radiation. 37 Although these studies demonstrated a very powerful platform for on-chip manipulation of photon emission, on-chip generation of multichannel photon emission with different intensities in each channel has not yet been realized, and the corresponding design approach is still elusive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The VSH application has resulted in significant progress comparing with previous directional but poorly polarized photon emission that was generated simply with QE-coupled Doppler bullseye nanoridges . Very recently, the VSH design strategy has been applied to realize on-chip integrated efficient generation of two well-collimated single-photon beams propagating along different off-normal directions with orthogonal linear polarizations, a complex functionality that can be assigned to a chip-integrated micronano single-photon polarization beam splitter . Moreover, the original VSH approach has further been extended and applied to realize quantum light sources for multichannel emission encoded with different spin and orbital angular momenta in each channel, extending multiple degrees of freedoms of QE radiation .…”
Section: Introductionmentioning
confidence: 99%